2024
DOI: 10.1093/mnras/stae1208
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of evolving low-frequency QPOs in hard X-rays (∼100 keV) observed in black hole Swift J1727.8−1613 with AstroSat

Anuj Nandi,
Santabrata Das,
Seshadri Majumder
et al.

Abstract: We report the first detection of evolving Low-Frequency Quasi-periodic Oscillation (LFQPO) frequencies in hard X-rays upto 100 keV with AstroSat/LAXPC during ‘unusual’ outburst phase of Swift J1727.8-1613 in hard-intermediate state (HIMS). The observed LFQPO in 20–100 keV has a centroid $\nu _{_{\rm QPO}}=1.43$ Hz, a coherence factor Q = 7.14 and an amplitude ${\rm rms_{_{\rm QPO}}} = 10.95{{\%}}$ with significance σ = 5.46. Type-C QPOs (1.09–2.6 Hz) are found to evolve monotonically during HIMS of the outburs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 51 publications
1
3
0
Order By: Relevance
“…Meanwhile, the hard X-ray flux measured by MAXI and Swift/BAT continues its descent. In Figure 2, we depict the HID of Swift J1727.8−1613, which aligns with the evolutionary trajectory obtained in previous studies (Nandi et al 2024;Peng et al 2024;Zhao et al 2024).…”
Section: Light Curves and Type C Qpos Of Swift J17278-1613supporting
confidence: 79%
“…Meanwhile, the hard X-ray flux measured by MAXI and Swift/BAT continues its descent. In Figure 2, we depict the HID of Swift J1727.8−1613, which aligns with the evolutionary trajectory obtained in previous studies (Nandi et al 2024;Peng et al 2024;Zhao et al 2024).…”
Section: Light Curves and Type C Qpos Of Swift J17278-1613supporting
confidence: 79%
“…However, in their work, they used a low energy resolution in producing the QPO rms spectra so that the characteristics of the HE rms excess is not clearly seen. Nandi et al (2024) studied the evolution of the QPO fractional rms with photon energy using AstroSat observations. However, they found that the QPO rms decreases from ∼13% at 20-40 keV to ∼2.5% at 80-100 keV, which is inconsistent with the trend we find.…”
Section: Discussionmentioning
confidence: 99%
“…Prominent type-C lowfrequency QPOs with frequencies ranging from ∼0.1 to ∼8 Hz were detected in Swift J1727.8-1613 based on a timing analysis of Insight-HXMT observations (Yu et al 2024;Zhu & Wang 2024). Nandi et al (2024) reported the first detection of type-C QPOs up to 80-100 keV using AstroSat/LAXPC data. In this Letter, we investigate the connection between the additional high-energy spectral component and the timing characteristics, and discuss the potential physical origin of this component.…”
Section: Introductionmentioning
confidence: 99%
“…This forms a "virtual" barrier around the BH, triggering the shock transition when possible. Indeed, accretion solutions containing shocks are thermodynamically preferred due to their high entropy content (Becker & Kazanas 2001), which facilitates the explanation of the spectrotemporal signatures of BH X-ray binaries (Chakrabarti & Titarchuk 1995;Mandal & Chakrabarti 2005;Nandi et al 2012;Iyer et al 2015;Das et al 2021;Majumder et al 2022;Nandi et al 2024). After realizing the astrophysical significance, shock-induced accretion solutions have been studied both in hydrodynamics (Fukue 1987;Chakrabarti 1989;Yang & Kafatos 1995;Ryu et al 1997;Lu et al 1999;Das et al 2001Das et al , 2014Das et al , 2009Becker & Kazanas 2001;Fukumura & Tsuruta 2004;Das 2007;Becker et al 2008;Kumar et al 2013;Suková & Janiuk 2015;Suková et al 2017;Aktar et al 2017;Kim et al 2019;Dihingia et al 2019;Sen et al 2022) as well as MHD (Takahashi et al 2006;Fukumura et al , 2016Sarkar & Das 2015, 2016 scenarios.…”
Section: Introductionmentioning
confidence: 99%